Empowerment-Based Relationship Management in CSR Communication: A Qualitative Study of Stakeholder Engagement in PT Pertamina Lubricants Gresik’s Kampung Iklim Program - Sasella, Mirel Imelda; Wulandari, Maulina Pia; Riani, Yuyun Agus (Tuturlogi: Journal of Southeast Asian Communication, 2025)
Strategic corporate communication plays a crucial role in fostering sustainable and empowering relationships between organizations and stakeholders, particularly within Corporate Social Responsibility (CSR) initiatives. This qualitative exploratory study investigates how the CSR Department of PT Pertamina Lubricants Production Unit Gresik (PUG) implements stakeholder engagement through the Kampung Iklim (ProKlim) program, an environmental initiative promoting community participation in climate adaptation and mitigation. Using Organization–Public Relationship Theory to explores how communication practices shape trust, satisfaction, commitment, and shared control in CSR implementation. Data were gathered through in-depth interviews, field observations, and document analysis, and analyzed using NVivo 12 Pro. Findings show that all five stages of stakeholder engagement are implemented but vary in maturity. The capacity strengthening stage remains weak, limiting long-term empowerment and relationship continuity, meanwhile action–review–reporting reflects strong transparency and accountability. Thematic analysis suggests that sustainable engagement emerges when communication evolves from one-way information delivery to dialogic, participatory, and empowerment-oriented interaction. This study proposes an Empowerment-Based Relationship Management Model, integrating dialogic communication, participatory capacity building, and mutual accountability as key elements of sustainable CSR communication, reframing CSR engagement as a co-creative process of empowerment and shared legitimacy.